2001
DOI: 10.1093/ije/30.4.818
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for non-Hodgkin's lymphoma according to family history of haematolymphoproliferative malignancies

Abstract: This study suggests differences in the risk factor profiles between NHL with and without a family history of HLPM. The higher risks of NHL for homosexual behaviour and heroin use, surrogates of HIV infection, in men with a family history of HLPM imply that genetic susceptibility may be influential on the occurrence of HIV-related NHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…It is plausible that NHL may cluster in families to some degree of shared environmental determinants, including various infectious agents, dietary habits, pesticides, and occupational exposure. 21,[38][39][40] However, a recent report from this database estimating the contribution of environmental effects comparing familial risks among siblings close or distant in age suggests that, in this population, the environmental component in the etiology of NHL and other lymphoproliferative malignancies is likely to play a marginal role. 38 Limited and inconsistent epidemiologic evidence is available on the familial risk for specific histopathologic subtypes of NHL.…”
Section: Discussionmentioning
confidence: 95%
“…It is plausible that NHL may cluster in families to some degree of shared environmental determinants, including various infectious agents, dietary habits, pesticides, and occupational exposure. 21,[38][39][40] However, a recent report from this database estimating the contribution of environmental effects comparing familial risks among siblings close or distant in age suggests that, in this population, the environmental component in the etiology of NHL and other lymphoproliferative malignancies is likely to play a marginal role. 38 Limited and inconsistent epidemiologic evidence is available on the familial risk for specific histopathologic subtypes of NHL.…”
Section: Discussionmentioning
confidence: 95%
“…Zhu et al 494 reported that NHL cases with a family history of HLP were more likely to report homosexual behavior, heroin use, nonhepatitis or noncirrhosis liver disease, work with plywood, exposure to chlorinated hydrocarbon pesticides, and enlarged lymph nodes 3 or more years prior to NHL diagnosis, as compared to cases without a family history. Except for working with plywood, the above associations were based on 10 or fewer cases with a family history of HLP.…”
Section: Interactions With Environment and Lifestyle Factorsmentioning
confidence: 99%
“…Except for working with plywood, the above associations were based on 10 or fewer cases with a family history of HLP. 494 Immune function and personal medical history Autoimmunity and immunodeficiency syndromes Several autoimmune disorders have been associated with increased risk of NHL, including rheumatoid arthritis (RA), celiac disease, systemic lupus erythematosus (SLE) and Sj€ ogren's syndrome; however, the proportion of cases of NHL associated with autoimmune disease is small, due to the low prevalence of autoimmune disorders in the general population. In a series of NHL patients included in a population-based lymphoma registry, 7.8% of patients exhibited clinical autoimmune phenomena, including RA (2.7%), Graves' disease (1.4%), and Sj€ ogren's syndrome (1.0%).…”
Section: Interactions With Environment and Lifestyle Factorsmentioning
confidence: 99%
“…The best established cause of NHL is impairment of immune function caused by primary immunodeficiency syndromes, immunosuppressive therapy in transplant patients, or human immunodeficiency virus (HIV) infection [3]. Other factors linked to greater risk of NHL include rheumatoid arthritis [4][5][6], history of allergy [7,8], family history of cancer [9,10], drug use such as phenytoin or chemotherapy [11][12][13], and pesticide exposure, especially the use of phenoxy herbicides [14,15].…”
Section: Introductionmentioning
confidence: 99%